Method for promoting low-temperature roasting of lepidolite hydrosulfate to extract lithium based on mechanical activation
By mechanically activating the mixture of lithium mica and bisulfate, reducing the calcination temperature and auxiliary materials, the problems of high energy consumption and excessive impurity leaching in the lithium mica lithium extraction process are solved, and efficient leaching of lithium in lithium mica is achieved.
Patent Information
- Application Number
- CN202411541441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In the existing lithium mica extraction process, the high calcination temperature and the high amount of auxiliary materials are used, resulting in high energy consumption and excessive impurities leaching, making it difficult to achieve efficient lithium leaching in lithium mica under low auxiliary materials ratio, low calcination temperature and water immersion conditions.
Using a method based on mechanical activation, the ball milling is activated by mixing lithium mica with bisulfate to reduce the calcination temperature and auxiliary materials, and efficient extraction of lithium is achieved during the water immersion process.
Under low auxiliary material ratio and low roasting temperature conditions, the leaching rate of lithium in lithium mica is significantly improved, energy consumption and production costs are reduced, and the leaching risk of impurity elements is reduced.
Smart Images

Figure CN119410912A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical smelting, and in particular to a method for extracting lithium by promoting low-temperature roasting of lepidolite hydrogen sulfate based on mechanical activation. Background Art
[0002] With the rapid development of the global new energy industry, the importance of lithium resources has become increasingly prominent. As one of the key raw materials for preparing battery-grade lithium carbonate, lithium mica has been included in the list of national strategic resources. At present, the lithium extraction process of lithium mica mainly includes a variety of technical routes such as pressure cooking, chlorination and sulfate roasting. Among them, the main process of sulfate roasting includes: first, crushing and floating the lithium mica ore to obtain lithium mica concentrate; then mix the concentrate with sulfate auxiliary materials in proportion, roast at high temperature to release lithium from the lithium mica, and the roasted clinker is dissolved in water through a water leaching process to form a lithium-containing leaching solution; finally, through a series of purification, concentration and lithium precipitation steps, battery-grade lithium carbonate is purified.
[0003] The Chinese invention patent application with publication number CN118479501A discloses a method for preparing lithium carbonate from lepidolite; the method comprises mixing lepidolite, sulfate, calcium hydroxide, sulfur, and water and pressing bricks, then drying the converted materials, and then roasting them at 870-950°C, and preparing lithium carbonate by crushing-leaching-impurity removal-extraction-lithium precipitation after roasting. Although lithium extraction from lepidolite is performed, the roasting temperature is relatively high, and the source of auxiliary materials is complicated, and other substances such as calcium hydroxide and sulfur are introduced, and the amount of sulfate used as an auxiliary material alone is not reflected.
[0004] In view of this, it is necessary to provide a method for extracting lithium by low-temperature roasting of lithium mica bisulfate based on mechanical activation, so as to solve or at least alleviate the technical problem of how to achieve efficient leaching of lithium from lithium mica under the conditions of low auxiliary material ratio, low roasting temperature and water leaching. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for extracting lithium by low-temperature roasting of lepidolite bisulfate based on mechanical activation, aiming to solve the above-mentioned technical problem of how to achieve efficient leaching of lithium from lepidolite under the conditions of low auxiliary material ratio, low roasting temperature and water immersion.
[0006] To achieve the above object, the present invention provides a method for extracting lithium by low-temperature roasting of lepidolite bisulfate based on mechanical activation, comprising the steps of:
[0007] S1, providing mixed materials;
[0008] The mixed material comprises lepidolite and hydrogen sulfate, and the mass percentage of the hydrogen sulfate and the lepidolite is 35-45%;
[0009] S2, performing mechanical activation treatment on the mixed material to obtain a precursor material;
[0010] The mechanical activation treatment comprises: ball milling the mixed material, wherein the ball-to-material ratio used in the ball milling is 2-6:1, the rotation speed of the ball milling is 500-800 rpm, and the ball milling time is 1.8-6 hours;
[0011] S3, calcining the precursor material to obtain a calcined clinker; the calcination temperature is 400-800° C., and the calcination time is not less than 30 minutes;
[0012] S4, sequentially subjecting the roasted clinker to water leaching and solid-liquid separation to obtain a lithium-containing leaching solution.
[0013] Furthermore, the lithium mica is lithium mica concentrate; the lithium mica concentrate contains lithium, iron, potassium, sodium, magnesium and calcium.
[0014] Furthermore, in the lithium mica concentrate, the mass proportion of the lithium element is 0.9-1.1%, the mass proportion of the iron element is 2-2.3%, the mass proportion of the potassium element is 7-7.2%, the mass proportion of the sodium element is 0.5-0.7%, the mass proportion of the magnesium element is 0.02-0.04%, and the mass proportion of the calcium element is 0.1-0.2%.
[0015] Furthermore, the lepidolite concentrate contains ferrolithium mica.
[0016] Furthermore, the mass percentage of the hydrogen sulfate and the lepidolite is 35-40%.
[0017] Furthermore, the bisulfate includes one or more of sodium bisulfate and potassium bisulfate.
[0018] Furthermore, the ball-to-material ratio used in the ball mill is 4-6:1, the rotation speed of the ball mill is 600-700rpm, and the ball milling time is 1.9-2.1h.
[0019] Furthermore, the calcination temperature is 600-650° C., and the calcination time is 80-120 min.
[0020] Furthermore, the duration of the immersion is not less than 60 minutes.
[0021] Furthermore, the water immersion process includes: placing the roasted clinker in water and shaking it; the solid-liquid ratio of the roasted clinker to the water is 1g:20-30mL.
[0022] The main principle description of the present invention includes:
[0023] The key to extracting lithium from lepidolite is to destroy its structure at high temperature, and then undergo a replacement reaction with the alkali metal in the sulfate to convert the insoluble interlayer lithium into soluble lithium for leaching; mechanical activation treatment can increase the specific surface area of lepidolite, providing more active sites for chemical reactions; mechanical activation can destroy the lattice structure of lepidolite, and collision and friction introduce strain and thermal effects, injecting additional energy into the crystal structure, causing it to undergo irregular changes; these changes may cause dislocations and defects in the lepidolite crystals, reduce its activation energy, and thus enhance its chemical activity, allowing its structure to be destroyed at a lower temperature.
[0024] In the present invention, the leaching rate of lithium is significantly improved after mechanical activation treatment after mixing. First, during the ball milling process, the mixing between lithium mica and auxiliary materials is more uniform, and some reactants have formed good contact and preliminary reaction after mixing, thereby improving the reaction activity of the subsequent roasting process; More importantly, the present invention strengthens the destruction of the lithium site structure in lithium mica by mixing lithium mica with specific auxiliary materials such as sodium bisulfate and then mechanically activating it. Analysis shows that during the activation process of the present invention, the lithium in the lithium mica migrates out from between the layers of its structure, so that the lithium exists in the precursor in the form of aluminosilicate, which is more susceptible to destruction by bisulfate in the subsequent roasting process, and finally exists in the form of sodium lithium sulfate; In addition, the present invention utilizes the water solubility of lithium-containing sulfates, and the roasted clinker can achieve efficient lithium extraction by simple water immersion.
[0025] It should be emphasized that the ball milling in the present invention does not only provide a mixing environment; the present invention co-ball mills the lepidolite and specific auxiliary materials such as sodium bisulfate, so that the lepidolite and sodium bisulfate can be pre-reacted under the conditions of ball milling; in combination with the embodiments of the present invention, after the co-ball milling, the intermediate product will change based on the pre-reaction of the lepidolite and sodium bisulfate, so that the lithium in the lepidolite can be efficiently leached after roasting at a lower temperature and with less auxiliary materials.
[0026] Compared with the prior art, the present invention has at least the following advantages:
[0027] The present invention can achieve efficient leaching of lithium from lithium mica under the conditions of low auxiliary material ratio, low roasting temperature and water immersion. Therefore, the present invention effectively controls the production cost and solves the problems of high roasting temperature, high energy consumption, large amount of slag and excessive impurity leaching in the traditional method. Specifically, the present invention is based on a method for promoting the low-temperature roasting of lithium mica bisulfate to efficiently extract lithium based on mechanical activation. It only needs to perform a simple mechanical activation treatment on the bisulfate and the lithium mica together, which can greatly reduce the reaction temperature and the amount of auxiliary materials required for roasting. The energy utilization efficiency is high, and the efficient leaching of lithium is guaranteed while reducing energy consumption. Moreover, the present invention only needs to use a simple and easy-to-operate water leaching method, which can greatly reduce the risk of leaching of impurity elements compared to other leaching methods such as acid leaching. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0029] Figure 1 This is a graph showing the change in lithium ion leaching rate in the leaching solution corresponding to each experiment in Example 1 of the present invention;
[0030] Figure 2 The phase composition diagram of the concentrate, activated concentrate, activated precursor after mixing (corresponding to activation after mixing in the figure), roasted clinker after mixing of activated concentrate, and roasted clinker after activation of mixing in Example 1 of the present invention;
[0031] Figure 3 This is a graph showing the change in lithium ion leaching rate in the leaching solution corresponding to mixing first and then activating (corresponding to mixing and then activating in the figure) and activating first and then mixing (corresponding to mixing and then activating in the figure) under the conditions of 40% auxiliary material (sodium bisulfate) and different roasting temperatures in Example 2 of the present invention;
[0032] Figure 4 This is a graph showing the change in lithium ion leaching rate in the leaching solution corresponding to different roasting temperatures under the condition that the auxiliary material (sodium bisulfate) accounts for 35% in Example 3 of the present invention;
[0033] Figure 5 This is a comparison diagram of lithium ion concentrations in the leachate corresponding to the lithium mica concentrate and the sodium bisulfate auxiliary material at different ball milling speeds in Example 4 of the present invention;
[0034] Figure 6 This is a comparison diagram of lithium ion concentrations in the leachate corresponding to the lepidolite concentrate and the sodium bisulfate auxiliary material at different ball-to-material ratios in Example 5 of the present invention;
[0035] Figure 7 This is a comparison diagram of lithium ion concentrations in the leachate corresponding to the lepidolite concentrate and the sodium bisulfate auxiliary material at different ball milling times in Example 6 of the present invention;
[0036] Figure 8 This is a comparison chart of lithium leaching rates in corresponding leaching solutions after roasting of lepidolite concentrate and different types of sulfates (auxiliary materials) in Example 7 of the present invention.
[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0040] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.
[0041] It should be noted that the Chinese invention patent application with publication number CN112624161A records a method for preparing lithium carbonate by extracting lithium from lithium mica by mechanical activation; the lithium mica concentrate powder and oxalic acid are weighed at a mass ratio of 3-6:1, and then added to a ball mill for ball milling and mixing for 24-48 hours to obtain a precursor powder, and the precursor powder is added to a rotary kiln for roasting at 600-800°C for 0.5-2 hours to obtain a roasting material; concentrated sulfuric acid is used to react with the roasting material at medium and low temperatures, and then the alkali metal sulfate is leached and dissolved with water; different crystallization inducers are added to continuously induce crystallization and impurity removal; finally, the obtained lithium hydroxide solution is reacted with carbon dioxide to prepare battery-grade lithium carbonate. Although it extracts lithium at a low auxiliary material ratio, ball milling activation and a relatively low roasting temperature; however, its activation process takes a long time, and the oxalic acid added in the activation process and the pre-reaction with concentrated sulfuric acid before water leaching will completely destroy the structure of the lithium mica, resulting in a large amount of leaching of other impurities in the mineral phase, which seriously increases the difficulty of subsequent leachate treatment. Therefore, the present invention requires a method for obtaining an efficient metallic lithium based on a system of bisulfate and water leaching.
[0042] The present invention provides a method for extracting lithium by promoting low-temperature roasting of lepidolite hydrogen sulfate based on mechanical activation, comprising the following steps:
[0043] S1, providing a mixed material.
[0044] In the present invention, the mixture includes or is lepidolite and bisulfate, the mass percentage of the bisulfate to the lepidolite is 35-45%, preferably 35-40%, specifically 39-41%; the bisulfate can be used as an auxiliary material alone, that is, only the bisulfate is mixed with the lepidolite.
[0045] In the present invention, the lepidolite is lepidolite concentrate; the lepidolite concentrate is derived from lepidolite ore, and the lepidolite ore is pre-treated with lithium to obtain the lepidolite concentrate, and the pre-treatment includes crushing, impurity removal, drying and other processes.
[0046] In the present invention, the lithium mica concentrate contains lithium, iron, potassium, sodium, magnesium and calcium. In the lithium mica concentrate, the mass proportion of the lithium element can be 0.9-1.1%, the mass proportion of the iron element can be 2-2.3%, the mass proportion of the potassium element can be 7-7.2%, the mass proportion of the sodium element can be 0.5-0.7%, the mass proportion of the magnesium element can be 0.02-0.04%, and the mass proportion of the calcium element can be 0.1-0.2%. The lithium mica concentrate also contains aluminum and silicon; the mass proportion of the aluminum element can be 14-15%, and the mass proportion of the silicon element can be 22-23%. The lithium mica concentrate also contains thallium and beryllium; the mass proportion of the thallium element can be 0.001-0.003%, and the mass proportion of the beryllium element can be 0.01-0.02%.
[0047] In the lithium mica of the present invention, the lithium element exists in the form of lithium oxide Li2O, the iron element exists in the form of iron oxide Fe2O3, the potassium element exists in the form of potassium oxide K2O, the sodium element exists in the form of sodium oxide Na2O, the magnesium element exists in the form of magnesium oxide MgO, the calcium element exists in the form of calcium oxide CaO, the aluminum element exists in the form of aluminum oxide, and the silicon element exists in the form of silicon dioxide; specifically, the lithium mica concentrate of the present invention contains lithium oxide, iron oxide, potassium oxide, sodium oxide, magnesium oxide, and calcium oxide; the remaining components mainly include aluminum oxide and silicon dioxide.
[0048] In the present invention, the mass proportion of the lithium oxide in the lithium mica concentrate can be 2-3%, the mass proportion of the iron oxide in the lithium mica concentrate can be 2-4%, the mass proportion of the potassium oxide in the lithium mica concentrate can be 8-9%, the mass proportion of the sodium oxide in the lithium mica concentrate can be 0.5-1%, the mass proportion of the magnesium oxide in the lithium mica concentrate can be 0.03-0.08%, and the mass proportion of the calcium oxide in the lithium mica concentrate can be 0.15-0.3%; in addition, the mass proportion of the aluminum oxide in the lithium mica concentrate can be 25-30%, and the mass proportion of the silicon dioxide in the lithium mica concentrate can be 45-50%. In the present invention, the main phases contained in the lithium mica concentrate include iron lithium mica K(AIFeLi)(Si3Al)O 10 (OH)F; the lithium mica concentrate has a lamellar structure.
[0049] In the present invention, the bisulfate includes or is one or more of sodium bisulfate and potassium bisulfate; as a preferred embodiment, the bisulfate is sodium bisulfate.
[0050] S2, mechanically activating the mixture to obtain a precursor material.
[0051] The lithium in the precursor material exists in the form of aluminosilicate (mainly in the form of aluminosilicate); the phase of the precursor material includes aluminosilicate, and the remaining phase is mainly sodium aluminum silicate and other mica phases; specifically, the precursor material contains KAl3Si3O 10 (0H)2, LiAlSiO4, NaAlSi3O8.
[0052] In the present invention, the mechanical activation treatment includes: ball milling (activation) the mixed material, the ball-to-material ratio (mass ratio) used in the ball milling is 2-6:1, preferably 4-6:1 or 5-6:1; the rotation speed of the ball milling is 500-800rpm, preferably 600-700rpm; the ball milling time is 1.8-6h or 2-6h, preferably 1.9-2.1h or 4.9-5.1h. Specifically, the ball-to-material ratio can be 5:1, the rotation speed of the ball milling can be 600rpm, and the ball milling time can be 2h.
[0053] S3, calcining the precursor material to obtain calcined clinker.
[0054] In the present invention, the calcination temperature is 400-800°C, and the calcination time is not less than 30 minutes; preferably, the calcination temperature is 500-800°C or 600-800°C or 600-700°C or 600-650°C or 500-600°C, and the calcination time is not less than 80 minutes or the calcination time is 80-120 minutes. Furthermore, the calcination temperature can be 600°C, and the calcination time can be 100 minutes.
[0055] As another illustration of an embodiment of the present invention, for the above-mentioned calcination temperatures and calcination times, the mass percentage of the bisulfate and the lepidolite can also be 35-37% or 40-45%; further, when the mass percentage of the bisulfate and the lepidolite is 35-37%, the calcination temperature can be 700-800°C or 600-700°C; when the mass percentage of the bisulfate and the lepidolite is 40-45%, the calcination temperature can be 600-620°C or 600-700°C or 600-800°C.
[0056] S4, sequentially subjecting the roasted clinker to water leaching and solid-liquid separation to obtain a lithium-containing leaching solution.
[0057] In the present invention, the water immersion can be carried out at 20-35°C, specifically at room temperature; the duration of the water immersion is not less than 60 minutes, and can further be 100-150 minutes. The water immersion process includes: placing the roasted clinker in water and shaking; the solid-liquid ratio of the roasted clinker to the water can be 1g:20-30mL.
[0058] The process flow of the invention is simple and has less environmental pollution. The invention realizes efficient lithium extraction under low auxiliary material ratio and low temperature roasting conditions through mechanical activation, significantly reduces the roasting temperature and auxiliary material dosage of the traditional sulfate roasting method, and reduces energy consumption and cost. The invention adopts a simple and easy-to-operate water leaching process, and the obtained lithium-containing leachate has low impurity content and a lithium leaching rate of more than 90%. The invention has broad application prospects in the field of lithium extraction by roasting lepidolite.
[0059] It should be noted that the existing research generally has the problem of high roasting temperature or the need for additional auxiliary conditions such as pressurization and microwaves; in addition, some methods use acid leaching or alkali leaching in the leaching step, which is not only complicated in process, but also may lead to a large amount of leaching of impurity elements. To this end, the present invention uses bisulfate as an auxiliary material and combines mechanical activation technology to treat the mixed material; under the conditions of low auxiliary material ratio and low temperature roasting, combined with water leaching process, efficient leaching of lithium is achieved; the present invention effectively controls the production cost and solves the problems of high energy consumption and high roasting temperature leading to sintering, large slag volume and excessive impurity leaching in traditional methods.
[0060] The following are specific examples of the present invention:
[0061] Example 1
[0062] This embodiment is a comparative analysis of the activation mode of lepidolite concentrate and sodium bisulfate mixture, and the specific implementation process is as follows:
[0063] Roasting of concentrate alone (Experiment 1): The lepidolite concentrate is roasted to obtain roasted clinker; the roasted clinker is leached in water, and a leaching solution and leaching residue are obtained after solid-liquid separation.
[0064] Activated concentrate roasted separately (Experiment 2): The lepidolite concentrate is ball-milled to obtain a ball-milled product; the ball-milled product is roasted to obtain a roasted clinker; the roasted clinker is water-leached to obtain a leachate and a leach residue after solid-liquid separation.
[0065] Roasting of concentrate mixture (Experiment 3): Mixing lepidolite concentrate and sodium bisulfate (auxiliary material) to obtain a mixture; roasting the mixture to obtain roasted clinker; leaching the roasted clinker in water, and obtaining a leachate and a leach residue after solid-liquid separation.
[0066] Activated concentrate followed by mixed material roasting (Experiment 4): ball milling the lepidolite concentrate to obtain a ball milling product; mixing the ball milling product with sodium bisulfate (auxiliary material) and roasting to obtain a roasted clinker; leaching the roasted clinker in water, and obtaining a leachate and a leach residue after solid-liquid separation.
[0067] Activated roasting after mixing (Experiment 5): Mix the lithium mica concentrate and sodium bisulfate (auxiliary material) to obtain a mixture; ball-mill the mixture to obtain a precursor material; roast the precursor material to obtain a roasted clinker; soak the roasted clinker in water, and obtain a leachate and a leach residue after solid-liquid separation.
[0068] The specific conditions in the above experiments are as follows:
[0069] When sodium bisulfate is involved, the mass of sodium bisulfate is 40% of the lepidolite concentrate;
[0070] When ball milling is involved, the process is completed in a planetary ball mill, the ball-to-material ratio used in the ball milling is 6:1, the speed of the ball milling is 500 rpm, and the ball milling time is 120 min;
[0071] When it comes to roasting, the roasting process is as follows: the material to be roasted is placed in a quartz crucible, and placed in a muffle furnace, the roasting temperature of the muffle furnace is set to be constant at 600°C, and the heat preservation time is 100 minutes; after the roasting is completed, it is taken out when the temperature cools to room temperature.
[0072] When water immersion and solid-liquid separation are involved, the implementation process of water immersion and solid-liquid separation is: at room temperature, pour the roasted clinker into a conical flask, inject pure water, the solid-liquid ratio of the roasted clinker and pure water is 1g:25mL, seal it and place it in a constant temperature shaking box (25°C) for shaking, take it out after shaking for 120 minutes, and filter it through a Buchner funnel.
[0073] The lepidolite concentrate used in this embodiment has a lamellar structure; in the lepidolite concentrate, the contents of some elements are shown in Table 1, and the contents of some components are shown in Table 2.
[0074] Table 1 Elemental analysis of lithium mica concentrate (mass %)
[0075] element Li Al Fe Si K Na Mg Ca TI Be content 1.05 14.77 2.16 22.58 7.09 0.58 0.03 0.16 0.002 0.0177
[0076] Table 2 Composition analysis of lithium mica concentrate (mass %)
[0077] Element <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO CaO <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[Fe2O3]]> <![CDATA[Li2O]]> content 27.9 48.3 0.05 0.22 0.78 8.54 3.09 2.27
[0078] In this example, the lithium ion leaching rate in the leaching solution corresponding to each of the above experiments was analyzed by ICP-OES. The specific results are as follows: Figure 1 shown.
[0079] analyze Figure 1 The results show that the lithium leaching rate in lithium mica concentrate increased from 1.85% (experiment 1: concentrate roasted alone) to 2.19% (experiment 2: activated concentrate roasted alone), indicating that mechanical activation destroyed the structure of the concentrate, thereby promoting the roasting reaction process; however, this increase was relatively limited, indicating that under the condition of roasting alone, the advantages brought by activation were not fully manifested. Under the condition of low sodium bisulfate dosage (40%), ball milling activation significantly increased the lithium leaching rate from 32.01% (experiment 3: concentrate mixed roasting) to 49.14% (experiment 4: activated concentrate followed by mixed roasting) and 90.57% (experiment 5: mixed roasting followed by activation), among which the method of mixing first and then activating showed the highest lithium leaching rate.
[0080] XRD analysis was performed on the concentrate (lepidolite concentrate), activated concentrate (ball milling product in Experiment 4), activated precursor after mixing (precursor material in Experiment 5), roasted clinker after mixing activated concentrate (roasted clinker in Experiment 4), and roasted clinker after mixing activated (roasted clinker in Experiment 5). The results are as follows: Figure 2 shown.
[0081] The analysis found that the phase composition of the concentrate is relatively simple, mainly ferrolithium mica. After the concentrate was activated alone, the phase did not change significantly, and was still dominated by ferrolithium mica, but its characteristic peak intensity decreased, and the corresponding θ angle shifted to the left, indicating that the activation process had a certain effect on the stability of the lithium mica structure, but it was not significant. From the phase analysis of the precursor obtained after mixing and activation, it can be seen that compared with the concentrate, the phase composition has changed significantly, the ferrolithium mica phase has basically disappeared, lithium mainly exists in the form of aluminum silicate, and the remaining phases are mainly sodium aluminum silicate and other mica phases; mechanical activation after mixing significantly enhances the activation effect of lithium mica, and the addition of auxiliary material sodium bisulfate further destroys the lithium sites in lithium mica, promotes the migration of interlayer lithium, and makes lithium stably exist in the precursor in the form of aluminum silicate, so that it is easier to react with sulfate during the subsequent roasting process. Analysis of the two roasted clinkers showed that lithium mainly exists in the form of sodium lithium sulfate, and there is no obvious difference.
[0082] The leaching liquid of the activated roasted clinker after mixing (corresponding to Experiment 5) was analyzed for impurity elements, and the results are shown in Table 3. It can be seen from the table that the leaching rates of the impurity elements are all at a low level, among which the leaching rates of the toxic elements thallium and beryllium are all around 1%, which is very ideal.
[0083] Table 3 Leaching rate of impurity elements
[0084] Impurity Elements Al Fe Si K Mg TI Be Leaching rate (%) 0.0026 0.0291 0.0135 19.53 27.63 1.2 1.4
[0085] Example 2
[0086] This example compares the lithium leaching conditions of two methods, namely, activation first and then mixing and mixing first and then activation, at different roasting temperatures under the condition that the auxiliary material accounts for 40%. The specific implementation process is as follows:
[0087] Compared with Experiment 4 in Example 1, the first activation and then mixing experiment in this embodiment has only a different calcination temperature, while other conditions remain the same.
[0088] Compared with Experiment 5 in Example 1, the first mixing and then activating experiment in this embodiment has only a different calcination temperature, while other conditions remain the same.
[0089] The experiments of activation first and then mixing and the experiments of mixing first and then activation in this embodiment were carried out at calcination temperatures of 400° C., 500° C., 600° C., 700° C., and 800° C., respectively.
[0090] In this example, the lithium ion leaching rate in the leaching solution corresponding to the first activation and then mixing experiment and the first mixing and then activation experiment was analyzed by ICP-OES. The specific results are as follows: Figure 3 shown.
[0091] analyze Figure 3It can be seen from the results that the lithium leaching rate gradually increases with the increase of roasting temperature. The increase in temperature promotes the reaction and allows the reactants to fully react. It is worth noting that when the temperature is 800°C, the lithium leaching rate in both methods exceeds 90%, which also shows that temperature is the key influencing factor that causes the destruction of the lithium mica structure to cause the transformation of interlayer lithium to soluble lithium. However, when the method of mixing first and then activating is selected for the experiment, the lithium leaching rate can reach about 90% at a lower temperature (600°C), while activating first and then mixing requires a higher temperature (800°C) to achieve a similar effect.
[0092] Example 3
[0093] This example compares the lithium leaching conditions corresponding to different roasting temperatures under the conditions of activation after mixing when the auxiliary material accounts for 35%. The specific implementation process is as follows:
[0094] In the experiment of this embodiment, compared with Experiment 5 in Example 1, only the proportion of sodium bisulfate and the roasting temperature were changed, and other conditions remained unchanged.
[0095] In this embodiment, the mass of sodium bisulfate is 35% of the lepidolite concentrate; and this embodiment is implemented at roasting temperatures of 400° C., 500° C., 600° C., 700° C., and 800° C., respectively.
[0096] In this example, the lithium ion leaching rate in the leaching solution was analyzed by ICP-OES. The specific results are as follows: Figure 4 shown.
[0097] analyze Figure 4 The results show that when the roasting temperature is between 400-500℃, the lithium leaching rate does not exceed 50%, which is at a low level. When the roasting temperature is between 600-800℃, the lithium leaching rate is greatly improved, 84.5% at 600℃ and 88.03% at 700℃; when the roasting temperature is 800℃, the lithium leaching rate exceeds 90%, reaching 92.03%.
[0098] Example 4
[0099] This example compares the lithium leaching rate of lithium mica and sodium bisulfate auxiliary materials at different ball milling speeds, and the specific implementation process is as follows:
[0100] In the experiment of this embodiment, compared with Experiment 5 in Example 1, only the proportion of sodium bisulfate and the rotation speed of the ball mill were changed, and other conditions remained unchanged.
[0101] In this embodiment, the mass of sodium bisulfate is 35% of the lepidolite concentrate; and this embodiment is implemented at ball milling speeds of 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, and 800 rpm, respectively.
[0102] In this example, the lithium ion leaching rate in the leaching solution was analyzed by ICP-OES. The specific results are as follows: Figure 5 shown.
[0103] analyze Figure 5 It can be seen from the results that in the low frequency band (300rpm), the treatment effect is poor, which may be due to insufficient mechanical energy, which cannot fully break the crystal structure of lithium mica, resulting in insufficient contact area and uniformity between sodium bisulfate and lithium mica, and the reaction activity of the activated precursor is low at this time; in the medium frequency band (400-600rpm), with the increase of frequency, the treatment effect is significantly improved, indicating that the mechanical activation intensity of this frequency band can effectively improve the reaction activity of the precursor; at 600-700rpm, the lithium leaching rate reaches the ideal value, exceeding 90%; however, when the ball mill speed is further increased to 800rpm, the lithium leaching rate decreases instead, indicating that further increasing the ball mill speed has limited effect, and may be affected by other factors (such as excessive wear or overheating) under high frequency conditions, thereby limiting the lithium leaching effect.
[0104] Example 5
[0105] This example compares the leaching rate of lithium from lepidolite and sodium bisulfate auxiliary materials at different ball-to-material ratios, and the specific implementation process is as follows:
[0106] During the experiment of this embodiment, compared with Experiment 5 in Example 1, only the proportion of sodium bisulfate, the rotation speed of the ball mill and the ball-to-material ratio were changed, and other conditions remained unchanged.
[0107] In this embodiment, the mass of sodium bisulfate is 35% of the lithium mica concentrate, and the rotation speed of the ball mill is 600 rpm; and this embodiment is implemented at ball-to-material ratios of 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, and 1:2, respectively.
[0108] In this example, the lithium ion leaching rate in the leaching solution was analyzed by ICP-OES. The specific results are as follows: Figure 6 shown.
[0109] analyze Figure 6 The results show that the lithium leaching rate changes when the ball-to-material ratio changes from 1:2 to 6:1. The leaching rate shows an upward trend, reaching a maximum value of 94.91% when the ball-to-material ratio is 5:1, and decreases slightly to 90.21% when the ball-to-material ratio is 6:1.
[0110] Low ball-to-material ratio (1:2, 1:1): When the ball-to-material ratio is low, the leaching rate is low, which is 36.49% and 41.89% respectively; this may be because when the ball-to-material ratio is low, the grinding effect is insufficient, resulting in poor mechanical activation effect, thus affecting the reaction; Medium ball-to-material ratio (2:1, 3:1, 4:1): As the ball-to-material ratio increases, the leaching rate increases significantly (68.7%, 84.55%, 88.87% respectively).
[0111] When the ball-to-material ratio is 5:1, the lithium leaching rate is as high as 94.91%. The increase in the amount of grinding media further enhances the activation of the concentrate. As the ball-to-material ratio further increases to 6:1, the leaching rate slightly decreases to 90.21%. This may be due to excessive grinding resulting in too fine particles, which in turn causes the reactants to accumulate, local overheating, or a reduction in the reaction surface, resulting in a decrease in the leaching rate.
[0112] Example 6
[0113] This example compares the leaching rate of lithium from lepidolite and sodium bisulfate auxiliary materials at different activation times, and the specific implementation process is as follows:
[0114] In the experiment of this embodiment, compared with Experiment 5 in Example 1, only the proportion of sodium bisulfate, the rotation speed of the ball mill and the time of the ball mill were changed, and other conditions remained unchanged.
[0115] In this embodiment, the mass of sodium bisulfate is 35% of the lithium mica concentrate, and the rotation speed of the ball mill is 600 rpm; and this embodiment is implemented at ball milling times of 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively.
[0116] In this example, the lithium ion leaching rate in the leaching solution was analyzed by ICP-OES. The specific results are as follows: Figure 7 shown.
[0117] analyze Figure 7 The results show that under short-time (1 hour) activation conditions, the effect is not obvious, which may be due to insufficient activation time, resulting in insufficient contact and reaction time between sodium bisulfate and lithium mica. As the activation time is extended to 2 hours, the reaction effect is significantly improved, indicating that appropriately extending the activation time enhances the transfer of mechanical energy, thereby effectively improving the reaction activity. However, after 2 hours (2-6 hours), the experimental effect tends to a plateau, the growth trend slows down, and tends to balance.
[0118] Example 7
[0119] This example compares the lithium leaching rate of lithium mica mixed with different sulfates at a roasting temperature of 500 degrees Celsius after the mixed materials are roasted. The specific implementation process is as follows:
[0120] The auxiliary material and the lithium mica concentrate (same as in Example 1) are mixed in a mass ratio of 2:1 to obtain a mixture; the mixture is placed in a quartz crucible and then placed in a muffle furnace, and the muffle furnace is set to have a constant roasting temperature of 500°C and a heat preservation time of 100 min; after the roasting is completed, the mixture is taken out when the temperature is cooled to room temperature to obtain a roasted clinker; the roasted clinker is poured into a conical flask, and pure water is injected, the solid-liquid ratio of the roasted clinker to the pure water is 1g:25mL, and the mixture is sealed and placed in a constant temperature shaking box (25°C) for shaking, and taken out after shaking for 60 min, and filtered through a Buchner funnel to obtain a lithium-containing leachate.
[0121] This embodiment is implemented under the condition that the auxiliary materials are sodium sulfate, ammonium sulfate, ammonium hydrogen sulfate, sodium hydrogen sulfate, calcium hydrogen sulfate, and potassium hydrogen sulfate.
[0122] In this example, the lithium ion leaching rate in the leaching solution was analyzed by ICP-OES. The specific results are as follows: Figure 8 shown.
[0123] analyze Figure 8 The results show that different types of sulfates have a significant impact on the leaching rate of lithium. When calcined at 500°C, the leaching rate of ammonium bisulfate is the lowest, about 12.34%; the leaching rate of lithium in the sodium sulfate system is 13.56%; the ammonium sulfate system is slightly improved, with a lithium leaching rate of 26.37%; the leaching rate in the calcium bisulfate system is 37.08%; and in the sodium bisulfate and potassium bisulfate systems, the lithium leaching rates reached 72.96% and 72.71%, respectively.
[0124] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for extracting lithium by low-temperature roasting of lepidolite bisulfate based on mechanical activation, characterized in that: Includes steps: S1, providing mixed materials; The mixed material comprises lepidolite and hydrogen sulfate, and the mass percentage of the hydrogen sulfate and the lepidolite is 35-45%; S2, performing mechanical activation treatment on the mixed material to obtain a precursor material; The mechanical activation treatment comprises: ball milling the mixed material, wherein the ball-to-material ratio used in the ball milling is 2-6:1, the rotation speed of the ball milling is 500-800 rpm, and the ball milling time is 1.8-6 hours; S3, calcining the precursor material to obtain a calcined clinker; the calcination temperature is 400-800° C., and the calcination time is not less than 30 minutes; S4, sequentially subjecting the roasted clinker to water leaching and solid-liquid separation to obtain a lithium-containing leaching solution.
2. The method for extracting lithium according to claim 1, characterized in that: The lithium mica is lithium mica concentrate; the lithium mica concentrate contains lithium, iron, potassium, sodium, magnesium and calcium.
3. The method for extracting lithium according to claim 2, characterized in that: In the lithium mica concentrate, the mass proportion of the lithium element is 0.9-1.1%, the mass proportion of the iron element is 2-2.3%, the mass proportion of the potassium element is 7-7.2%, the mass proportion of the sodium element is 0.5-0.7%, the mass proportion of the magnesium element is 0.02-0.04%, and the mass proportion of the calcium element is 0.1-0.2%.
4. The method for extracting lithium according to claim 2, characterized in that: The lithium mica concentrate contains ferrolithium mica.
5. The method for extracting lithium according to claim 1, characterized in that: The mass percentage of the hydrogen sulfate and the lepidolite is 35-40%.
6. The method for extracting lithium according to claim 1, characterized in that: The bisulfate salt includes one or more of sodium bisulfate and potassium bisulfate.
7. The method for extracting lithium according to claim 1, characterized in that: The ball-to-material ratio used in the ball mill is 4-6:1, the rotation speed of the ball mill is 600-700 rpm, and the ball milling time is 1.9-2.1 h.
8. The method for extracting lithium according to claim 1, characterized in that: The calcination temperature is 600-650° C., and the calcination time is 80-120 min.
9. The method for extracting lithium according to claim 1, characterized in that: The duration of the immersion is not less than 60 minutes.
10. The method for extracting lithium according to any one of claims 1 to 9, characterized in that: The water immersion process comprises: placing the roasted clinker in water and shaking; the solid-liquid ratio of the roasted clinker to the water is 1g:20-30mL.
Citation Information
Patent Citations
Method for preparing lithium carbonate by mechanically activating lepidolite to extract lithium
CN112624161A
Method for preparing lithium carbonate from lepidolite
CN118479501A
Method for treating lithium-containing minerals through mineral element phase transfer
CN110117020A
Process method for ultra-efficient deep extraction of lithium from lepidolite
CN114751433A
Process of lithium extraction from ores and concentrates by mechanical activation and reaction with sulphuric acid
WO2017200408A1
Cited By
Method for efficiently extracting lithium by roasting lepidolite at low temperature by using composite organic acid
CN120818704A
Method for extracting lithium from lepidolite
CN122303627A